Vanadium lithium silicate all-solid-state lithium battery and preparation method thereof

CN116779981BActive Publication Date: 2026-10-23SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310789190.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2026-10-23
Estimated Expiration
2043-06-30

AI Technical Summary

Benefits of technology

[0026] The main inventive point of this invention lies in the first-time use of Li₂VSiO₅ material to replace lithium cobalt oxide and ternary layered oxide cathode materials, and the preparation of both cathode and anode materials with LLZO solid electrolyte via co-sintering technology. Since the heat treatment temperature of Li₂VSiO₅ is very close to that of LLZO solid electrolyte (900-1000 °C), co-sintering technology can be used for electrode preparation. This invention also prepares an LLZO||Li₂VSiO₅@LLZO composite electrode via a casting method, which has advantages such as low interfacial impedance, simple preparation process, and easy industrialization. Furthermore, this invention uses LLZO as the solid electrolyte, which has excellent compatibility with lithium metal and lithium metal composite materials as anodes, thereby constructing an all-solid-state lithium secondary battery that exhibits high energy density and excellent safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779981B_ABST
    Figure CN116779981B_ABST
Patent Text Reader

Abstract

The application discloses a kind of vanadium lithium silicate full solid-state lithium battery and preparation method thereof, preparation method includes: with garnet solid electrolyte LLZO according to certain mass ratio, with dispersing agent is mixed in ethanol / toluene mixed solution and is made into slurry, thin film is prepared by flow casting method;At 950~1100 ℃ solid phase sintering, obtain Li2VSiO5 / LLZO composite pole piece;LLZO, dispersing agent etc. are dispersed in ethanol / toluene mixed solution and made into slurry, with Li2VSiO5 / LLZO composite pole piece as substrate, thin film is prepared by flow casting method;At 950~1100 ℃ solid phase sintering, obtain LLZO||Li2VSiO5@LLZO composite pole piece;With lithium metal etc. Material is used as negative electrode, and is obtained by assembling.According to the application, a kind of vanadium lithium silicate full solid-state lithium battery with high capacity, large rate, good high-low temperature performance, high safety is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of secondary battery technology, and more specifically to a lithium vanadium silicate all-solid-state lithium battery and its preparation method. Background Technology

[0002] Replacing traditional fossil fuels with renewable energy is crucial for achieving carbon neutrality and peak carbon emissions. The efficient utilization of clean energy sources such as wind and solar power relies heavily on the development and application of large-scale energy storage systems. Among various energy storage systems, electrochemical energy storage systems hold promise for large-scale applications due to their high volumetric and gravimetric energy density and flexible installation. Lithium-ion batteries, with their excellent electrochemical performance, have been widely used in portable electronic devices, electric vehicles, and large-scale energy storage. Currently, most widely used lithium-ion batteries employ liquid electrolytes. The organic solvents in liquid electrolytes are flammable, posing certain safety risks to the batteries. Furthermore, most organic solvents undergo side reactions with lithium metal, making it impossible to use lithium metal as the negative electrode and limiting the energy density of lithium batteries. Solid-state batteries, constructed using solid electrolytes instead of traditional liquid electrolytes, offer advantages such as non-flammability, high-temperature resistance, non-corrosiveness, non-volatility, and good compatibility with lithium metal. All-solid-state lithium batteries possess advantages such as high safety and high energy density, making them one of the important development directions for next-generation lithium-ion batteries.

[0003] Among numerous solid-state electrolyte systems, the inorganic solid-state ceramic electrolyte lithium lanthanum zirconium oxide (Li7La3Zr2O) stands out. 12 , LLZO (Lithium-ion-cobalt oxide) possesses advantages such as low cost, high safety, ease of operation, high air stability, and a wide electrochemical window, making it a crucial electrolyte material in solid-state batteries and a promising candidate for large-scale application in the future. However, LLZO has a synthesis temperature exceeding 1000 °C, limiting its use in most lithium-ion secondary battery cathode materials, such as lithium cobalt oxide and ternary layered compounds like LiNiCo. 1-x Mn 1-y The synthesis temperature of oxygen (O) is below 800℃. This significant temperature difference poses a serious challenge to the construction of the cathode. Current solutions involve adding a sintering aid during the co-sintering process to lower the sintering temperature, successfully constructing a high-performance composite cathode. However, adding a sintering aid affects ion transport in the electrode and also increases cost and reduces the energy density of the battery system.

[0004] In 2018, Wang et al. added the sintering aid Li... 2.3 C 0.7 B 0.3O3 was used to construct a lithium cobalt oxide / lithium lanthanum zirconium oxide solid electrolyte composite cathode, and the sintering temperature was reduced to 700 °C. This was then matched with lithium metal anode materials to construct an all-solid-state lithium metal battery. This battery exhibited high safety, high voltage, and good cycle stability. Reference: Han FD, Yue J, Chen C, et al. Interphase Engineering Enabled All-Ceramic Lithium Battery [J]. JOULE, 2018, 2(3): 497-508.

[0005] In 2020, Xia et al. added the sintering aid Li... 2.985 B 0.005 OCl was used to construct a lithium cobalt oxide / lithium lanthanum zirconium oxide solid electrolyte composite cathode, reducing the sintering temperature to 400 °C. When matched with lithium metal anode materials, an all-solid-state lithium metal battery was constructed that could stably cycle 50 times at 90 °C. Reference: Feng WL, Lai ZZ, Dong XL, et al. Garnet-Based All-Ceramic Lithium Battery Enabled by Li 2.985 B 0.005 OCl Solder[J].ISCIENCE, 2020, 23(5): 101071.

[0006] In 2006, Tarascon et al. synthesized Li₂VOSiO₄ using a solid-state method and studied its electrochemical performance as a cathode material for lithium-ion batteries. In liquid electrolyte, the average operating potential of this material as a lithium-ion battery cathode material was 3.6 V vs. Li / Li. + The discharge specific capacity at C / 10 rate is 100 mAh / g. Reference: Chem. Mater. 2006, 18, 407-412.

[0007] In 2008, Wan Chunrong et al. disclosed a method for preparing lithium vanadium silicate, a cathode material for lithium-ion batteries. This method involves preparing a precursor by reacting lithium, vanadium, silicon, and carbon sources via a sol-gel reaction. After drying, the precursor is subjected to high-temperature heat treatment at 600-900 °C for 8-48 hours under an inert and reducing atmosphere to obtain lithium vanadium silicate powder. The resulting lithium vanadium silicate powder consists of nanoscale particles, exhibiting good conductivity and high specific capacity. At a 1 C rate, the reversible specific capacity is greater than 160 mAh / g in the 3-4.8V charge-discharge range, and greater than 285 mAh / g in the 1.5-4.8V charge-discharge range, with excellent cycle performance. However, this method constructs a liquid lithium battery. See Chinese patent application CN200810117701.8.

[0008] However, a common problem with the aforementioned existing technologies is the significant difference between the synthesis temperature of traditional lithium-ion battery cathode materials and the synthesis temperature of LLZO solid electrolytes, leading to substantial challenges in constructing composite cathode electrodes. While the addition of sintering aids can lower the sintering temperature, it also brings serious side effects, such as potentially reducing lithium-ion conductivity, lowering system energy density, and increasing cost. The fundamental reason is that the sintering temperature of common cathode materials is below 800℃, while the synthesis temperature of solid electrolyte LLZO is above 1000℃; however, this is determined by the Gibbs free energy of material formation and cannot be controlled. Although Li₂VOSiO₄ cathode materials with high synthesis temperatures exhibit good electrochemical performance, the vast majority of reported data comes from traditional liquid lithium-ion batteries using organic liquid electrolytes. Summary of the Invention

[0009] The purpose of this invention is to provide a lithium vanadium silicate all-solid-state lithium battery and its preparation method, thereby solving the problem of the huge difference between the synthesis temperature of the cathode material and the synthesis temperature of the solid electrolyte in the prior art, as well as the huge challenge in the construction of the cathode composite electrode.

[0010] To solve the above problems, the present invention adopts the following technical solution:

[0011] According to a first aspect of the present invention, a method for preparing a lithium vanadium silicate all-solid-state lithium battery is provided, comprising the following steps: S1: using Li2VSiO5 as the positive electrode material, and reacting it with a garnet-type solid electrolyte (Li7La3Zr2O) 12S1: LLZO is mixed at a mass ratio of (60~90):(10~40), and conductive agent, dispersant, plasticizer, and binder are added and dispersed in an ethanol / toluene mixed solution to form a slurry. A thin film is prepared by casting. S2: After drying at 80~120℃, it is isostatically pressed and then solid-state sintered at 950~1100℃ for 5~20 h to obtain the Li2VSiO5 / LLZO composite electrode. S3: Solid electrolyte LLZO, dispersant, plasticizer, and binder are dispersed in an ethanol / toluene mixed solution to form a slurry. A thin film is prepared by casting using the Li2VSiO5 / LLZO composite electrode as a substrate. S4: After drying at 80~120℃ and isostatically pressed, the thin film is solid-state sintered at 950~1100℃ for 5~20 h. h, an LLZO||Li2VSiO5@LLZO composite electrode can be obtained; S5: Using any one of lithium metal, lithium metal composite material, graphite, and silicon-carbon composite material as the negative electrode, and the LLZO||Li2VSiO5@LLZO composite electrode as the positive electrode, an all-solid-state lithium vanadium silicate battery is assembled.

[0012] In step S1, the Li2VSiO5 includes: undoped Li2VSiO5 and doped Li2VSiO5, such as cathode materials obtained by doping with Na, Ge, Mn, Fe, Ni, Nb, Ti, etc., with the general chemical formula Li2M 2-a2 VN 1-b SiX 1-c O5 (where M represents Group 1 elements such as Na, K, and H; N represents transition metal elements such as Ni, Co, Fe, and Mn; and X represents non-metallic elements including Ge and P). It should be understood that doping modification is a very mature technology and is widely used in the research of battery electrode materials. For details, please refer to the literature Electrochemistry Communications 8 (2006) 1553–1557; Electrochimica Acta 50 (2005) 2955–2958; CN105870432B; CN103594686A.

[0013] In step S1, the solid electrolyte LLZO includes: undoped LLZO and doped LLZO, including Nb doping, Al doping, Mn doping, oxygen vacancy doping, etc. It should be understood that LLZO doping modification is a very mature technology and is widely used in the research of battery electrode materials. For details, please refer to J. Mater. Chem. A, 2014, 2, 13431-1343; Electrochimica Acta 180 (2015) 37–42; Scientific Reports | 5:18053 | DOI: 10.1038 / srep18053; CN115732752A; CN115924971A.

[0014] Preferably, in step S1, the thickness of the film prepared by the casting method should be as thick as possible, approximately between 200-500 μm. A thickness less than 200 μm results in low positive electrode loading and low energy density, while a thickness greater than 500 μm results in high internal resistance and poor performance. Preferably, in step S3, the thickness of the film prepared by the casting method is 50-200 μm. A thickness less than 50 μm results in insufficient mechanical strength, while a thickness greater than 200 μm results in excessively low battery energy density.

[0015] Preferably, in step S1, Li2VSiO5 and solid electrolyte LLZO are mixed at a mass ratio of (60~90):(10~40). If the content of Li2VSiO5 is less than 60%, the energy density of the battery may be too low, while if it is more than 90%, the ionic conductivity of the positive electrode may be too low.

[0016] Preferably, in steps S1 and S3, the sintering temperature is 950-1100℃. If the temperature is too low, the density of the prepared electrode will be insufficient and the internal resistance will be too high. If the sintering temperature is higher than 1100℃, the LLZO electrolyte Li will volatilize, reducing the ionic conductivity.

[0017] In steps S1 and S3, the dispersant includes silicates and alkali metal phosphates; the binder includes vinylidene fluoride, styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate; the conductive agent includes conductive graphite, conductive carbon black, carbon fiber, carbon nanotubes, graphene, and composite conductive paste; and the plasticizer includes phthalate, propylene glycol adipate polyester, butyl epoxy ester, and fish oil.

[0018] Preferably, in steps S1 and S3, the solid content of the prepared slurry is 55-75%.

[0019] Preferably, in step S4, the isostatic pressure is 50-120 MPa.

[0020] Preferably, in step S4, the assembly of the lithium vanadium silicate all-solid-state lithium battery is completed in a glove box or a drying chamber (H2O content less than 1ppm).

[0021] According to a second aspect of the present invention, a lithium vanadium silicate all-solid-state lithium battery prepared according to the preparation method is provided.

[0022] As described in the background section of this invention, the most commonly used cathode materials in solid-state lithium secondary batteries are lithium cobalt oxide and layered ternary compounds. These materials are typically synthesized at temperatures below 800°C, significantly lower than the synthesis temperature of LLZO solid electrolytes (above 1000°C), thus posing a considerable challenge to the construction of the cathode in all-solid-state lithium batteries. Adding sintering aids, such as Li... 2.3 C 0.7 B 0.3 O3, Li 2.985 B 0.005 OCl can lower the sintering temperature to some extent, such as 600℃ or even lower. However, the addition of sintering aids reduces the energy density of the system and also increases the preparation cost and complicates the preparation process.

[0023] To overcome the problems and challenges of existing solid-state lithium secondary batteries, this invention provides a Li2VSiO5 all-solid-state lithium battery and its preparation method. Through repeated screening and optimization of cathode materials, the inventors ultimately determined that Li2VSiO5 is an ideal cathode material for lithium-ion batteries, with a synthesis temperature of approximately 1000℃. Since the synthesis temperatures of Li2VSiO5 and LLZO solid electrolyte are very close, the two materials exhibit excellent compatibility. This invention is the first to use Li2VSiO5 cathode material to replace traditional lithium-ion battery cathode materials, employing co-sintering technology to directly construct a Li2VSiO5 / LLZO composite electrode. Combined with LLZO solid electrolyte and lithium metal anodes, a high-performance all-solid-state lithium secondary battery is ultimately constructed. Compared to existing publicly reported systems, the solid-state lithium secondary battery constructed in this invention does not require the addition of any sintering aids and features simple processing and excellent performance.

[0024] It should be understood that the raw material Li₂VSiO₅ used in this invention is a known material that can be synthesized by a solid-state method. High-purity Li₂VSiO₅ can be obtained by using lithium silicate and vanadium dioxide as raw materials, through solid-state ball milling, pressing, and high-temperature sintering. Since this Li₂VSiO₅ material is existing technology, it will not be described in detail here; for more information, please refer to Chem. Mater. 2006, 18, 407-412.

[0025] This invention obtains a high thermal stability lithium vanadium silicate (Li2VSiO5) cathode material (synthesis temperature around 1000℃) through screening. The cathode is constructed by co-sintering with LLZO solid electrolyte (sintering temperature can be around 1000℃), and the cathode is constructed with the anode to form an all-solid-state lithium secondary battery. This battery system has advantages such as high safety, low cost, simple process, and excellent performance, and is a solid-state lithium secondary battery with great application prospects.

[0026] The main inventive point of this invention lies in the first-time use of Li₂VSiO₅ material to replace lithium cobalt oxide and ternary layered oxide cathode materials, and the preparation of both cathode and anode materials with LLZO solid electrolyte via co-sintering technology. Since the heat treatment temperature of Li₂VSiO₅ is very close to that of LLZO solid electrolyte (900-1000 °C), co-sintering technology can be used for electrode preparation. This invention also prepares an LLZO||Li₂VSiO₅@LLZO composite electrode via a casting method, which has advantages such as low interfacial impedance, simple preparation process, and easy industrialization. Furthermore, this invention uses LLZO as the solid electrolyte, which has excellent compatibility with lithium metal and lithium metal composite materials as anodes, thereby constructing an all-solid-state lithium secondary battery that exhibits high energy density and excellent safety performance.

[0027] The biggest differences between this invention and existing articles or patents are: 1) The use of Li2VSiO5 cathode material in a solid-state battery system, unlike the previously used lithium cobalt oxide or ternary cathode materials; Li2VSiO5 cathode material has a capacity of 160 mAh / g, a high sintering temperature, and good compatibility with LLZO solid electrolyte; 2) The sintering method involved in this invention does not require the addition of any sintering aid, and the synthesized cathode composite electrode has very low interfacial impedance; 3) The Li2VSiO5 solid-state lithium secondary battery constructed in this invention is different from any existing all-solid-state lithium battery system, and is a completely new type of solid-state lithium secondary battery; 4) This invention applies Li2VSiO5 cathode material to solid-state lithium batteries, unlike the technical solutions reported in previous articles or patents for use in liquid electrolyte systems.

[0028] In summary, the vanadium silicate lithium solid-state lithium battery and its preparation method provided by the present invention have the following advantages compared with the prior art:

[0029] According to the method of the present invention, a composite electrode can be constructed by a simple co-sintering technique without the need to add any sintering aid. The process is simple, and the sintering temperature of the Li2VSiO5 cathode material is basically the same as that of the solid electrolyte LLZO. The prepared composite cathode exhibits good electrochemical performance, including high capacity, high rate capability and good high and low temperature performance.

[0030] The lithium-ion battery cathode material used in this invention is Li2VSiO5 cathode material. Compared with other cathode materials, such as LiCoO2 and layered ternary materials, the raw materials used in its synthesis are lithium silicate (Li2SiO3) and vanadium dioxide (VO2), which are inexpensive and have a cost advantage.

[0031] The solid electrolyte LLZO used in this invention has high safety and good compatibility with the negative electrode material, and the constructed all-solid-state lithium secondary battery has high safety. Attached Figure Description

[0032] Figure 1 A schematic diagram of a Li||LLZO|| Li2VSiO5@LLZO all-solid-state lithium metal battery prepared in Example 1 is shown.

[0033] Figure 2 A schematic diagram of a graphite or silicon-carbon ||LLZO|| Li2VSiO5@LLZO all-solid-state lithium-ion battery prepared in Example 2 is shown.

[0034] Figure 3 A schematic diagram of a Li|| doped LLZO|| Li2VSiO5@ doped LLZO all-solid-state lithium metal battery prepared in Example 3 is shown.

[0035] Figure 4 A schematic diagram of a Li||LLZO|| doped Li2VSiO5@LLZO all-solid-state lithium-ion battery prepared in Example 4 is shown. Detailed Implementation

[0036] The present invention will be further described below with reference to specific embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, the technical means used in the embodiments are conventional operations in the art, and the reagents and raw materials used in the embodiments are commercially available unless otherwise specified.

[0037] Example 1:

[0038] Li₂VSiO₅ is used as the positive electrode material and mixed with solid electrolyte LLZO at a mass ratio of 80:20. A conductive agent (carbon black), dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder are added and dispersed in an ethanol / toluene mixture to prepare a slurry. After removing air bubbles, a thin film is prepared by casting. Specifically, Li₂VSiO₅, LLZO powder, organic binder, dispersant, and solvent solution are mixed in appropriate proportions to prepare a slurry with a certain viscosity (viscosity is expressed as solid content, which is generally 55-75%). The slurry flows uniformly from a container and is coated onto a special substrate at a certain thickness by a doctor blade. After drying and curing, a film precursor is obtained (casting machine model GT06002-3, China).

[0039] After drying at 100℃, the film is isostatically pressed and then solid-state sintered at 950℃ for 10 hours to obtain the composite electrode. Using the Li2VSiO5 / LLZO composite electrode as a substrate, a pure LLZO solid electrolyte layer with a thickness of 50-200 μm is deposited on this substrate via a casting method. The solid electrolyte slurry is prepared by dispersing solid electrolyte LLZO, dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder in an ethanol / toluene mixed solution. After removing air bubbles, a film is cast on the Li2VSiO5 / LLZO composite electrode. Then, the film is dried at 100℃, isostatically pressed, and then solid-state sintered at 950℃ for 10 hours to obtain the LLZO||Li2VSiO5@LLZO composite electrode. A schematic diagram of the Li||LLZO||Li2VSiO5@LLZO all-solid-state battery, using lithium metal as the negative electrode material, is shown below. Figure 1 As shown.

[0040] This battery exhibits a reversible capacity greater than 100 mAh / g and an output voltage greater than 3.6 V at a C / 10 rate (Table 1). Figure 1 As shown, in addition to lithium metal, it also includes lithium metal composite anode materials, including Li-C (carbon), Li-Zn, Li-Al, Li-Cu, Li-Ag, etc.

[0041] Example 2:

[0042] Li₂VSiO₅ was used as the positive electrode material and mixed with solid electrolyte LLZO at a mass ratio of 70:30. A conductive agent (carbon black), dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder were added and dispersed in an ethanol / toluene mixed solution to prepare a slurry. After removing air bubbles, a thin film was prepared by casting. The film was dried at 100℃. After isostatic pressing, it was solid-state sintered at 950℃ for 10 hours to obtain the composite electrode. Using the Li₂VSiO₅ / LLZO composite electrode as a substrate, a pure LLZO solid electrolyte layer with a thickness of 50-200 μm was coated onto this substrate by casting. The solid electrolyte slurry was prepared as follows: solid electrolyte LLZO, dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder were dispersed in an ethanol / toluene mixed solution to prepare a slurry. After removing air bubbles, a film was cast on the Li₂VSiO₅ / LLZO composite electrode. Then, the film is dried at 100℃, and after isostatic pressing, it is solid-state sintered at 950℃ for 10 hours. This yields the LLZO||Li2VSiO5@LLZO composite electrode. Using graphite (silicon-carbon composite material) as the anode material, a graphite anode or silicon-carbon composite ||LLZO||Li2VSiO5@LLZO all-solid-state lithium-ion battery is assembled, as shown in the schematic diagram. Figure 2 As shown.

[0043] At C / 10 rate, the battery exhibits a reversible capacity of over 100 mAh / g and an output voltage of over 3.4 V.

[0044] Example 3:

[0045] Using Li₂VSiO₅ as the positive electrode material, the solid electrolyte is doped-modified LLZO (doped-LLZO), including Nb doping, Al doping, Mn doping, and oxygen vacancies. The solid electrolyte and doped-LLZO are mixed at a mass ratio of 90:10. A conductive agent (carbon black), a dispersant (fish oil), a plasticizer (dibutyl phthalate), and a cellulose binder are added and dispersed in an ethanol / toluene mixture to form a slurry. After removing air bubbles, a thin film is prepared by casting. It is dried at 100℃. After isostatic pressing, it is solid-state sintered at 950℃ for 10 hours to obtain the composite electrode. Using the Li₂VSiO₅ / doped-LLZO composite electrode as a substrate, a pure doped LLZO solid electrolyte layer with a thickness of 50-200 μm is cast onto this substrate. The solid electrolyte slurry was prepared by dispersing solid electrolyte LLZO, dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder in an ethanol / toluene mixed solution. After removing air bubbles, a film was cast onto a Li₂VSiO₅ / doped LLZO composite electrode. The film was then dried at 100°C, isostatically pressed, and then solid-state sintered at 950°C for 10 hours. This yielded the LLZO||Li₂VSiO₅@doped LLZO composite electrode. A schematic diagram of the Li||doped LLZO||Li₂VSiO₅@doped LLZO all-solid-state battery, using lithium metal as the anode material, is shown below. Figure 3 As shown.

[0046] This battery exhibits a reversible capacity greater than 100 mAh / g and an output voltage exceeding 3.6 V at a C / 10 rate. Figure 3 As shown, in addition to lithium metal, it also includes negative electrode materials that are composites with lithium metal, including Li-C (carbon), Li-Zn, Li-Al, Li-Cu, Li-Ag, etc.

[0047] Example 4:

[0048] Lithium vanadium silicate (Li₂VSiO₅) cathode is a doped Li₂VSiO₅. This includes cathode materials doped with Na, Ge, Mn, Fe, and Ni, with the general chemical formula Li₂M₂. 2-a2 VN 1-b SiX 1-cO5, where M represents Group 1 elements such as Na, K, and H, N represents transition metal elements such as Ni, Co, Fe, and Mn, and X represents non-metallic elements including Ge and P. It should be understood that this doping modification of Li2VSiO5 is a well-established and mature technology, widely used in the research of battery electrode materials. The positive electrode material and solid electrolyte are mixed at a mass ratio of 60:40. A conductive agent (carbon black), dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder are added and dispersed in an ethanol / toluene mixed solution to form a slurry. After removing air bubbles, a thin film is prepared by casting. After drying at 100℃, it is sintered in solid state at 950℃ for 10 hours to obtain the composite electrode. Using the doped Li2VSiO5 / LLZO composite electrode as a substrate, a solid electrolyte layer with a thickness of 50-200 μm is coated onto this substrate by casting. The solid electrolyte slurry was prepared by dispersing solid electrolyte LLZO, dispersant (fish oil), plasticizer (dibutyl phthalate), and cellulose binder in an ethanol / toluene mixed solution. After removing air bubbles, a film was cast onto a doped Li₂VSiO₅ / LLZO composite electrode. After drying at 100℃, it was sintered at 950℃ for 10 hours to obtain the LLZO|| doped modified Li₂VSiO₅@LLZO composite electrode.

[0049] Assembly and testing of all-solid-state batteries. Using lithium metal as the anode material, an all-solid-state battery (Li||LLZO|| doped and modified Li2VSiO5@LLZO) was assembled. Figure 4 This battery exhibits a reversible capacity greater than 110 mAh / g and a plateau potential above 3.6 V at a C / 10 rate. (Table 1) In addition to lithium metal, it also includes negative electrode materials composited with lithium metal, including Li-C (carbon), Li-Zn, Li-Al, Li-Cu, Li-Ag, etc.

[0050] Table 1: Comparison of electrochemical performance of all-solid-state lithium secondary batteries using different positive electrode materials, negative electrode materials, and solid electrolytes.

[0051]

[0052] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. Various variations can be made to the above embodiments of the present invention. All simple and equivalent changes and modifications made in accordance with the claims and description of this application fall within the protection scope of the claims of this patent. All aspects not described in detail in this invention are conventional technical content.

Claims

1. A method for preparing a lithium vanadium silicate all-solid-state lithium battery, characterized in that, Includes the following steps: S1: Using Li2VSiO5 as the positive electrode material, it is mixed with solid electrolyte LLZO at a mass ratio of (60~90):(10~40), and conductive agent, dispersant, plasticizer, and binder are added and dispersed in an ethanol / toluene mixed solution to form a slurry, which is then used to prepare a thin film by casting. S2: After drying at 80~120℃ and isostatic pressing, solid-state sintering at 950~1100℃ for 5~20 h can yield Li2VSiO5 / LLZO composite electrode. S3: Solid electrolyte LLZO, dispersant, plasticizer, and binder are dispersed in an ethanol / toluene mixed solution to form a slurry. A thin film is prepared by casting using a Li2VSiO5 / LLZO composite electrode as the substrate. S4: After drying at 80~120℃ and isostatic pressing, solid-state sintering at 950~1100℃ for 5~20 h can obtain LLZO||Li2VSiO5@LLZO composite electrode sheet; S5: Using any one of lithium metal, lithium metal composite material, graphite, and silicon-carbon composite material as the negative electrode, and the LLZO||Li2VSiO5@LLZO composite electrode as the positive electrode, a lithium vanadium silicate all-solid-state lithium battery is assembled.

2. The preparation method according to claim 1, characterized in that, In step S1, the Li2VSiO5 is undoped or doped Li2VSiO5, and the doping modification includes: Na doping, Ge doping, Mn doping, Fe doping, Ni doping, Nb doping, and Ti doping.

3. The preparation method according to claim 1, characterized in that, In step S1, the solid electrolyte LLZO is undoped or doped LLZO, and the doping modification includes Nb doping, Al doping, Mn doping, and oxygen vacancies.

4. The preparation method according to claim 1, characterized in that, In step S1, the thickness of the film prepared by the casting method is 200-500 μm.

5. The preparation method according to claim 1, characterized in that, In step S3, the thickness of the film prepared by the casting method is 50-200 μm.

6. The preparation method according to claim 1, characterized in that, In steps S1 and S3, the dispersant includes silicates and alkali metal phosphates; the binder includes vinylidene fluoride, styrene-butadiene rubber latex, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile, and polyacrylate; the conductive agent includes conductive graphite, conductive carbon black, carbon fiber, carbon nanotubes, graphene, and composite conductive paste; and the plasticizer includes phthalate, propylene glycol adipate polyester, epoxy ester butyl ester, and fish oil.

7. The preparation method according to claim 1, characterized in that, In steps S1 and S3, the solid content of the prepared slurry is 55-75%.

8. The preparation method according to claim 1, characterized in that, In step S4, the isostatic pressure is 50-120 MPa.

9. The preparation method according to claim 1, characterized in that, Step S4: Complete the assembly of the lithium vanadium silicate all-solid-state lithium battery in a glove box or drying chamber.

10. A lithium vanadium silicate all-solid-state lithium battery prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Production method of high-magnification long service life lithium ion battery anode material TiN phase doped LiFePO4

    CN103594686A

  • A method for preparing multi-site co-doped LiFePO4 / C by ultrasonic spraying of phosphate fertilizer products

    CN105870432B

  • Nb-doped LLZO solid electrolyte and preparation method thereof

    CN115732752A

  • Ga and Nb co-doped LLZO and preparation method thereof

    CN115924971A

  • Preparation of lithium ionic cell positive electrode material vanadium lithium silicate

    CN101339992A